Organizational Environment and Organizational Citizenship Behavior as Factors Influencing the Supervisory Performance Inspectorate of the Kolaka Regency - Tawai, Adrian; Munadi, La Ode Muh.; Khabiirun, Khabiirun; Samiel, Edy; Zumail, La Ode (Journal of Posthumanism, 2025)
An organizational environment is essential to supporting individual and group performance. A supportive work environment can create a positive climate, increase work enthusiasm, and improve team member performance. In addition to the organizational climate, individual Behaviour or Organizational Citizenship Behavior (OCB) also plays a vital role in improving supervisory performance. Based on the findings, it can be concluded that the organizational environment and organizational citizenship behaviour (OCB) both positively affect the supervisory performance of the Inspectorate of the Kolaka Regency. Variations in supervisory performance values ​​can be explained mainly by the organizational environment and OCB variables. The better the organizational climate and OCB, the better the supervisory performance of the Inspectorate of the Kolaka Regency.